1998
DOI: 10.1093/tropej/44.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Brief report. Malaria prevalence and outcome in the in-patients of the paediatric department of the state specialists hospital (SSH), Maiduguri, Nigeria

Abstract: Of 4651 admissions between February 1995 and February 1996, 1043 had a presumed diagnosis of malaria. Six hundred and twenty-seven cases were confirmed by thick blood film examinations. The highest prevalence was in October (124/480 admissions) and the lowest in March (12/303). Sixty-five children died while 562 survived, 12 with defects. The first treatment in 422 children was chloroquine, in 143 quinine, in 59 halofantrin, and in three pyrimethamine with sulfadoxine (Fansidar). 23/422 patients started on chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
4
1
Order By: Relevance
“…The number of deaths in this study is similar to reports from elsewhere in Africa [29][30][31][32][33][34][35][36] and similar also to the rate reported by a previous study in this hospital unit. 23 28 0.833 * Excluding children who died; ** excluding those discharged with fever and those who died with fever; † excluding those who died in a coma and those who never became comatose group died within the 1st 5 hours.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The number of deaths in this study is similar to reports from elsewhere in Africa [29][30][31][32][33][34][35][36] and similar also to the rate reported by a previous study in this hospital unit. 23 28 0.833 * Excluding children who died; ** excluding those discharged with fever and those who died with fever; † excluding those who died in a coma and those who never became comatose group died within the 1st 5 hours.…”
Section: Discussionsupporting
confidence: 91%
“…The rate of gross neurological sequelae is in the range of values described in some other trials 23,31,34,42,43 but lower than in others. [44][45][46] However, the numbers are too small and do not allow rm conclusions.…”
Section: Discussionmentioning
confidence: 44%
“…This value is higher than the previously reported range of 2% to 17% [9,14,17,18] but lower than other studies in adults which reported incidence ranging from 63% to 70% [10,13]. The different figures from previous studies could be due to the fact that haemoglobinuria was diagnosed only by visual inspection of the urine samples, or the inclusion of all malaria cases as the denominator.…”
Section: Discussioncontrasting
confidence: 73%
“…A multicentre study [17] of severe malaria among children in 10 African countries, Nigeria inclusive, reported a mean haemoglobinuria prevalence of 3.3%. Similarly, a prospective study of 627 children with confirmed diagnosis of malaria in Maiduguri, Nigeria, found haemoglobinuria in 3.7% of the patients [18]. A common problem of these studies is that they do not indicate the number of severe malaria patients included in the analyses.…”
Section: Introductionmentioning
confidence: 99%
“…[11] At a secondary-level health centre in the same city, 61.6% of its paediatric out-patients were positive for malaria parasite; [12] and of all admissions into its Paediatric ward, 22.4% had a presumptive diagnosis of malaria while 13.5% had been confirmed by thick blood film microscopy. [13] Malaria had also accounted for 44.8% of admissions into the Emergency Paediatric Unit of a tertiary health centre in north-eastern Nigeria and also was also the cause of 49.6% of deaths occurring in the unit. [14] Malaria infection in children has also been reported to be a risk factor for anaemia.…”
Section: Introductionmentioning
confidence: 99%